2022
DOI: 10.3390/ijms23031037
|View full text |Cite
|
Sign up to set email alerts
|

2-Acetamido-2-deoxy-d-glucono-1,5-lactone Sulfonylhydrazones: Synthesis and Evaluation as Inhibitors of Human OGA and HexB Enzymes

Abstract: Inhibition of the human O-linked β-N-acetylglucosaminidase (hOGA, GH84) enzyme is pharmacologically relevant in several diseases such as neurodegenerative and cardiovascular disorders, type 2 diabetes, and cancer. Human lysosomal hexosaminidases (hHexA and hHexB, GH20) are mechanistically related enzymes; therefore, selective inhibition of these enzymes is crucial in terms of potential applications. In order to extend the structure–activity relationships of OGA inhibitors, a series of 2-acetamido-2-deoxy-d-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Considering that NAG products were typically recommended via oral administration for an adult at a dose of 20 mg/kg/day (an equivalent amount of less than 0.2 mg/kg/day tin in BNAGs) 10 , it is concluded that BNAGs would be very safe agents as either dietary supplements or medical drugs. To our knowledge, only several chemical modifications of NAG have been published, including replacement of 6-hydroxyl by deoxy, fluoro, thiol group or amino substituents 13 , functionalization of 1-hydroxyl to produce a library of 2-acetamido-2-deoxy-D-glucono-1,5-lactone arenesulfonylhydrazones 16 , as well as single or multiple acetylation 12 . As such, BNAG1 and BNAG2 were the bi-deoxygenated derivatives of NAG reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that NAG products were typically recommended via oral administration for an adult at a dose of 20 mg/kg/day (an equivalent amount of less than 0.2 mg/kg/day tin in BNAGs) 10 , it is concluded that BNAGs would be very safe agents as either dietary supplements or medical drugs. To our knowledge, only several chemical modifications of NAG have been published, including replacement of 6-hydroxyl by deoxy, fluoro, thiol group or amino substituents 13 , functionalization of 1-hydroxyl to produce a library of 2-acetamido-2-deoxy-D-glucono-1,5-lactone arenesulfonylhydrazones 16 , as well as single or multiple acetylation 12 . As such, BNAG1 and BNAG2 were the bi-deoxygenated derivatives of NAG reported for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in accordance with our current and previously reported data 21 . Furthermore, several NAG derivatives with different 1-hydroxyl substitutions have been proven as OGA inhibitors which could lead to an accumulation of protein O-GlcNAc 16 , 25 27 . As such, we hypothesize that NAG, BNAG1 and BNAG2 might suppress immune response through the inhibition of OGA, and the reason why BNAG1 displays better activity than BNAG2 or NAG is due to its 1-deoxygenation.…”
Section: Discussionmentioning
confidence: 99%